Gender in film and video - King, Neal, 1963-; Streeter, Rayanne; Rose, Talitha; Herling, Jessica (Routledge, Taylor & Francis Group, 2019)
"Gender in Film and Video analyzes gender in media focusing on six instances of media in transition. They show the changes in media as brought about by the internet age, such as crowdfunding and DIY filmmaking, while reviewing the top-down production of film and television retrospectively. The breakdown of the categories (content, production, reception) that top-down production/distribution in TV and cinema tended to keep distinct will be a major focus of this volume. This jargon-free text is written for undergraduates in sociology and media studies"- Resumé vydavatel
Keywords: gender; masmédia; filmová produkce -- sociální aspekty; filmová režie -- sociální aspekty; televizní produkce -- sociální aspekty; televizní režie -- sociální aspekty; digitální média -- sociální aspekty; televizní pořady -- sociální aspekty; mass media; film production -- social aspects; film direction -- social aspects; television production -- social aspects; television direction -- social aspects; digital media -- social aspects; television programs -- social aspects; monografie; monographs